PSYCHO-SOCIAL AND DEMOGRAPHIC FACTORS AS CORRELATES OF PERCEIVED ORGANISATIONAL PERFORMANCE IN SOUTHWESTERN NIGERIAN POLYTECHNICS (2014)
Polytechnic education which is considered crucial in the development of middle level technical manpower in Nigeria is dependent among other factors on the quality and level of its perceived organisational performance (POP), which has however not been stable over time. The dwindling POP has been attributed to some psycho-social and demographic variables and these have affected the accomplishment of the vision and mission of the polytechnics, particularly in Southwestern Nigeria. Previous studies have concentrated more on the influence of leadership styles, personality traits, employees job satisfaction and commitment without considering the prediction of psycho-social and demographic factors on the polytechnics POP. Therefore, this study examined the extent to which psycho-social (mentoring, communication, work-self efficacy, motivation, organisational citizenship behaviour, innovative work behaviour) and demographic factors (educational qualification, work experience, and gender) when combined can predict perceived organisational performance in polytechnics in Southwestern Nigeria. The study adopted the survey research design. The multi-stage random sampling technique was used to select 769 senior and 184 junior staff from 12 polytechnics accredited by the National Board for Technical Education. Seven instruments were used: Organisational Citizenship Behaviour Scale (r=0.82), Perceived Work-Self Efficacy Scale (r=0.81), Motivation Scale (r=0.76), Superior-Subordinate Communication Scale (r=0.82), Superior-Subordinate Mentoring Scale (r=0.94), Innovative Work Behaviour Scale (r=0.68) and POP Scale (r=0.90). These were complemented with two sessions of Key Informant Interviews in each of the 12 institutions with heads of departments (12) and principal officers (12). Two research questions were answered and three hypotheses tested at 0.05 level of significance. Data were subjected to Pearson Product Moment Correlation, multiple regression and content analysis. Psycho-social and demographic factors significantly correlated with POP in polytechnics (F (9,953) =64.03; p<0.05) and jointly accounted for 38.0% of the variation in the dependent variable. Psycho-social factors contributed about 37.1% while demographic factors had less than 1.0%. The relative contributions of psycho-social factors to POP were: innovative work behaviour (?=.28, p<0.05), mentoring (?=.22, p<0.05), organisational citizenship behaviour (?=.15, p<0.05), communication (?=.13, p<0.05); though work-self efficacy and motivation did not contribute to the dependent measure. Among the demographic factors only educational qualification contributed to the dependent measure (?=.02, p<0.05); while gender and working experience did not. POP correlated with psycho-social factors as follows: innovative work behaviour (r=0.52, p<0.05), mentoring (r=0.52, p<0.05), communication (r=0.48, p<0.05), organisational citizenship behaviour (r=0.34, p<0.05), motivation (r=0.31, p<0.05) and work-self efficacy (r=0.30, p<0.05). Further, POP did not correlate with any of the demographic factors. Seventy percent of the interviewees indicated that the polytechnics work environment rely mostly on informal mentoring, with little or no opportunities for creativities, innovations and learning on the job, a situation which is not fairly conducive for POP. Innovative work behaviour, mentoring, organisational citizenship behaviour and communication positively contributed to perceived organisational performance in polytechnics in Southwestern Nigeria. A proper understanding and enhancement of these psycho-social factors with learning opportunities are necessary in promoting optimal organisational performance. There is also the need to promote creativity, innovation and formal mentoring system among the staff.